Early Onset Seizures Beget Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The long-term effect of early-life seizures on later seizure-induced neuronal damage and behavior was investigated in the laboratory using systemic kainate to induce seizures in rats at the Massachusetts General Hospital, Boston, MA.